Clinical evaluation of dengue and identification of risk factors for severe disease: protocol for a multicentre study in 8 countries - Jaenisch, Thomas; Hoai Tam, Dong Thi; Thanh Kieu, Nguyen Tan; Ngoc, Tran Van; Tran Nam, Nguyen; Kinh, Nguyen Van; Yacoub, Sophie; Chanpheaktra, Ngoun; Kumar, Varun; Chai See, Lucy Lum; Sathar, Jameela; Sandoval, Ernesto Pleités; et al. (© 2016 BMC Infectious Diseases, 2018)
This article was published in the BMC Infectious Diseases [© Jaenisch et al. 2016] and the definite version is available at : https://doi.org/10.1186/s12879-016-1440-3 . The Journal's website is at: https://bmcinfectdis.biomedcentral.com/articles/10.1186/s12879-016-1440-3